1975
DOI: 10.2307/1366221
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Teleonomic Investigation of Avian Brood Parasitism

Abstract: The term "teleonomy" has been suggested by Williams (1966:258) to describe the scientific study of adaptations. Williams indicated that relatively few evolutionary studies deal primarily with teleonomy despite the fact that adaptation is the most basic feature of evolution and of all biology. Avian brood parasitism, the phenomenon in which certain birds, the parasites, deposit their eggs in the nests of other birds, their hosts, is especially well suited to teleonomic studies since it provides a system in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
322
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(329 citation statements)
references
References 32 publications
(10 reference statements)
7
322
0
Order By: Relevance
“…Therefore, egg removal by female cowbirds may serve to reduce clutch size and hence increase its egg's chances of hatching sooner, especially in larger host species. Rothstein (1975) suggested that Brown-headed Cowbirds may have initially parasitized larger host species. The strategy of egg removal may have allowed cowbirds to increase their chances of successfully parasitizing a larger host species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, egg removal by female cowbirds may serve to reduce clutch size and hence increase its egg's chances of hatching sooner, especially in larger host species. Rothstein (1975) suggested that Brown-headed Cowbirds may have initially parasitized larger host species. The strategy of egg removal may have allowed cowbirds to increase their chances of successfully parasitizing a larger host species.…”
Section: Discussionmentioning
confidence: 99%
“…Although cowbird nestlings often hatch before host nestlings because of a short incubation period (Briskie and Sealy 1990), nestling age was standardized in experiments (see below) to control for developmental stage because differences of only 1-2 days in age can markedly influence the begging behaviors of nestlings and their ability to compete for food (Khayutin 1985). It should be noted that the thrasher typically rejects cowbird eggs placed in its nest (Rothstein 1975), although thrashers do occasionally raise cowbirds on the study site (J. W. Rivers, unpublished data). However, inclusion of the thrasher is warranted in this study because it was the only available large species that fulfilled the goal of isolating host size as a focal variable.…”
Section: Study Area and Host Speciesmentioning
confidence: 99%
“…As predicted, there was no evidence for recognition: host and foreign chicks did not differ in survival rate (Figure 2f; Wilcoxon signed-rank test on proportion of non-template chicks surviving, W = 7.0, n = 15, two-tailed P = 0.57) or in parental feeding rate (Wilcoxon signed-rank test, W = 12.0, n = 15, twotailed P = 0.32). The design of the "mixed synchrony" experiments also enabled us to test and reject an alternative explanation for the patterns of rejection that we observed in the "host first" and "foreign first" experiments: recognition of the majority phenotype 26 (see Supplementary Information for details).…”
mentioning
confidence: 99%